GAMBARAN PENGGUNAAN BALUTAN LUKA KRONIS BERDASARKAN KARAKTERISTIK LUKA - Hidayat, Taufiq; Yusuf, Saldy; Nur Isnah, Wa Ode (Universitas Islam Negeri Alauddin Makassar, 2023)
Currently, wound dressings consist of many types and have different functions. However, the many types of dressings available make it challenging to select the dressing used for wounds (Mustamu et al., 2020). This study aims to determine the description of the use of chronic wound dressings based on wound characteristics. This research design uses a quantitative research design with a retrospective approach. The instrument used in this research was the DMIST observation sheet. The primary dressing used most often at the beginning of wound care is wound half: The first primary dressing in 19 cases (26.0%) and the second primary dressing in 44 cases (60.3%). Meanwhile, the secondary dressing most often used at the beginning of the visit was gauze, as the first secondary dressing in 27 cases (37.0%) and the second secondary dressing in 42 cases (57.5%). Meanwhile, at the end of the treatment process, the first primary dressing was dominated by half of the wounds in 30 cases (41.1%) and the second primary dressing in 28 cases (38.4%). Meanwhile, the most frequently used secondary dressing was gauze in 18 cases (24.7%). In conclusion, the primary dressing widely used in wound care is wound zalf. The secondary dressing is dominated by gauze. Keywords: Wound Dressing, Wound Care, Wound Characteristics, Chronic Wound